Faktor-faktor yang berhubungan dengan kinerja tenaga kesehatan dalam pelayanan antenatal care terpadu - Elisa Christiana; Sulchan Sofoewan; Herlin Fitriani Kurniawati (Universitas Aisyiyah Yogyakarta, 2016)
Abstract: The aim of research to find out the factors related to theperformance of health workers in ANC Integrated in Blitar. This study isa qualitative research with cross-sectional approach. Technique ofsampling with a total sampling found 40 health workers and 3 head ofPuskesmas. The results showed the performance of health workers inANC Integrated categorized 52.5% less, Factors related to theperformance of that age, leadership, attitude and motivation, while factorsunrelated are working time and supervision. The most dominant factorrelated to the performance is leadership after the controlled variablemotivation.Keywords: